Assessing the potential vulnerability of sedimentary carbon stores to bottom trawling disturbance within the UK EEZ - Black, Kirsty E.; Smeaton, Craig; Turrell, William R.; Austin, William E. N. (Frontiers in Marine Science, 2022)
It is estimated that within the UK exclusive economic zone (UK EEZ), 524 Mt of organic carbon (OC) is stored within seabed sediment. However, the stability and potential vulnerability of OC in these sediments under anthropogenic stressors, such as bottom trawling activity, remains poorly quantified. To improve our understanding of the areas where sedimentary OC is likely to be at greatest risk from trawling events, we have developed a carbon vulnerability ranking (CVR) to identify areas of the seabed where preventative protection may be most beneficial to help maintain current OC stocks while further research continues to shed light on the fate of OC after trawling (e.g., remineralization, transport, and consumption). Predictive maps of currently available fishing intensity, OC and sediment distribution, and sediment OC lability have been generated within ArcGIS using fuzzy set theory. Our results show that the west coast of Scotland represents one of the key areas where sedimentary OC is potentially at greatest risk from bottom trawling activity. This is due mainly to the high reactivity of these OC rich sediments combined with the pressures of repetitive trawling activity within inshore waters. Our research shows that these OC hotspots are potentially at risk of disturbance from bottom trawling activity and should be prioritized for the consideration of future safeguarding (management) measures to ensure emissions are minimized and to provide greater protection of this natural carbon capital resource.